Too depressed to breathe: The longitudinal association between depressive symptoms and lung function among general middle-aged and older adults. (November 2022) - Guo, Lizhi; Yang, Li; Rao, Liwei; Luo, Fengping; Gao, Ningcan; Jia, Xiaohua; Yu, Bin
Highlights: It is rational to clarify whether changes in pulmonary function over time are associated with baseline depression levels among older populations without lung diseases. Depressive symptoms were significantly associated with peak expiratory flow (PEF) among general middle-aged and older adults. The association between depressive symptoms and PEF was greater for men than for women. Abstract: Objective Most previous studies focusing on the association between depressive symptoms and lung function were conducted in patients with chronic lung diseases. This study aims to investigate the association of depressive symptoms with lung function among general Chinese middle-aged and older adults. Participants This study used data from the China Health and Retirement Longitudinal Study (CHARLS). Analyses were conducted with data from three waves (2011, 2013, and 2015) and restricted to those respondents aged 45 and older. Finally, 9487 individuals [mean age (SD) = 58.47 (9.19); female, 53.1%] were included in analysis. Methods Depressive symptoms were measured by the Chinese version of 10-item Center for Epidemiological Studies Depression Scale (CESD-10). Lung function was assessed by peak expiratory flow (PEF). Two-level linear mixed growth models were used to evaluate the longitudinal association between depressive symptoms and PEF. Results Depressive symptoms were significantly associated with PEF among general middle-aged and older adults ( b = − 1.85, p < 0.001) after adjusting for multiple confounding factors. A significant interaction between depressive symptoms and gender was found ( b = 1.29, p < 0.001). The association between depressive symptoms and PEF was greater for men ( b = − 2.36, p < 0.001) than for women ( b = − 1.46, p < 0.001). Conclusions This longitudinal study found that increased depressive symptoms were associated with reduced PEF in middle-aged and older adults in China. Compared with women, men with a higher level of depressive symptoms experienced a greater decrement in PEF. Our findings suggest that it is possible to reduce the effects of PEF by improving psychological health among general middle-aged and older populations.